2007
DOI: 10.1111/j.1440-1819.2007.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Sitting balance as an early predictor of functional improvement in association with depressive symptoms in stroke patients

Abstract: The aim of the present study was to assess the relationship between sitting balance at an early stage and activities of daily living (ADL) function in 452 stroke patients. The effect of sitting balance on the two core elements of depression (apathy and depressive mood) was also examined. The ability to maintain a sitting position for 10 min (10-min sitting balance) was assessed, along with ADL using the Functional Independence Measurement, and psychological status using the Zung Selfrating Depression Scale (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…32,33 According to Kwakkel and colleagues, 34 control of the trunk in the first week post-stroke, was an independent variable for predicting comfortable ambulation at 6 months. Hama and colleagues 35 conducted a study with 452 patients, aiming to verify the association of trunk control, depressive symptoms, and functional outcomes. The authors concluded that inefficient trunk control is strongly associated with depression, deficit of initiative and apathy, and predicts a worse functional outcome.…”
Section: -22mentioning
confidence: 99%
“…32,33 According to Kwakkel and colleagues, 34 control of the trunk in the first week post-stroke, was an independent variable for predicting comfortable ambulation at 6 months. Hama and colleagues 35 conducted a study with 452 patients, aiming to verify the association of trunk control, depressive symptoms, and functional outcomes. The authors concluded that inefficient trunk control is strongly associated with depression, deficit of initiative and apathy, and predicts a worse functional outcome.…”
Section: -22mentioning
confidence: 99%
“…12,13,16 The BRS scale defines recovery only in broad categories; these categories correlate with progressive functional recovery.…”
Section: Functional Measuresmentioning
confidence: 99%
“…[11][12][13][18][19][20] Patients completed the AS within 1 month after admission. The AS consists of 14 questions concerning spontaneity, initiation, emotionality, activity level, and interest in hobbies.…”
Section: Apathy Scalementioning
confidence: 99%
See 2 more Smart Citations